THE ROLE OF FOREIGN INVESTMENTS IN THE DEVELOPMENT OF THE REGIONAL ECONOMY (Web of Teachers: Inderscience Research, 2025)
This article discusses the importance of investments, in particular foreign investments, in the economic development of the region, the work being done to attract investments, the efforts made to take the region's place in world trade.